Directional hydrophone clusters reveal evasive responses of small cetaceans to disturbance during construction at offshore windfarms - Graham, I. M.; Gillespie, D.; Gkikopoulou, K. C.; Hastie, G. D.; Thompson, P. M. (Biology Letters, 2023)
Funding: This study was funded by Moray Offshore Wind Farm (East) Ltd. Mitigation measures to disperse marine mammals prior to pile-driving include acoustic deterrent devices and piling soft starts, but their efficacy remains uncertain. We developed a self-contained portable hydrophone cluster to detect small cetacean movements from the distributions of bearings to detections. Using an array of clusters within 10 km of foundation pile installations, we tested the hypothesis that harbour porpoises (Phocoena phocoena) respond to mitigation measures at offshore windfarm sites by moving away. During baseline periods, porpoise movements were evenly distributed in all directions. By contrast, animals showed significant directional movement away from sound sources during acoustic deterrent device use and piling soft starts. We demonstrate that porpoises respond to measures aimed to mitigate the most severe impacts of construction at offshore windfarms by swimming directly away from these sound sources. Portable directional hydrophone clusters now provide opportunities to characterize responses to disturbance sources across a broad suite of habitats and contexts. Peer reviewed